2018
DOI: 10.1021/acsami.8b19590
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Adsorption Separation of CO2/C2H2 Mixture in Cyclodextrin-Based Metal–Organic Frameworks

Abstract: The demand for CO 2 /C 2 H 2 separation, especially the removal of CO 2 impurity, continues to grow because of the high-purity C 2 H 2 required for various industrial applications. The adsorption separation of C 2 H 2 and CO 2 via porous materials is gaining a considerable attention as it is more energy-efficient compared with cryogenic distillation. The ideal porous materials are those that preferentially adsorb CO 2 over C 2 H 2 ; however, very few adsorbents meet such requirement. Herein, two isostructural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 50 publications
3
121
0
Order By: Relevance
“…In these cases, the open metal and basic positions are considered to be the origin for the behavior of selective adsorption. Former studies on the porous materials have shown that functional positions and appropriate pore dimension can improve the separation property [15][16][17][18][19]. In comparison with the open metal positions, the basic positions such as nitrogen-donor and oxygen-donor sites are less discussed for the separation of C 2 H 2 / CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the open metal and basic positions are considered to be the origin for the behavior of selective adsorption. Former studies on the porous materials have shown that functional positions and appropriate pore dimension can improve the separation property [15][16][17][18][19]. In comparison with the open metal positions, the basic positions such as nitrogen-donor and oxygen-donor sites are less discussed for the separation of C 2 H 2 / CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In literature reports to date, the capture of CO 2 over C2 hydrocarbons has so far largely been restricted to cryogenic temperatures and/or static conditions [52][53][54][55]57,61 . With respect to CO 2 /C 2 H 2 mixtures at ambient temperatures, we are aware of only a few reported materials, CD-MOF-1 51 , CD-MOF-2 51 58 for which this inverse trapping of CO 2 has been verified by experimental breakthrough measurements. Since these MOFs adsorb C 2 H 2 (in addition to CO 2 ) strongly at moderate pressures, their uptake ratios are modest.…”
Section: Resultsmentioning
confidence: 84%
“…While only a few nanoporous materials have been reported for the stripping of CO2 from H2/CO2 feedstocks, [45][46] as required for the purification of syngas, this has been identified as a high priority. [47][48] In this light, we conducted breakthrough studies for a 15/85 mixture of CO2/H2 at 293 K and 1.1 bar to show that MUF-16 is able to efficiently separate CO2 from H2. CO2 was retained on the MUF-16 bed while the H2 11 component eluted immediately in a high purity stream, as expected on the basis of the low uptake capacity for this gas (Figure 6d).…”
Section: Selectivity Of Muf-16 For Co2 and Gas Separationsmentioning
confidence: 99%